Energy Storage Reservoir Management System For Wsn With Solar Harvesting - Amran, Nur Amira (2016)
Most of the study in managing power on wireless sensor network node (WSN) is mainly on how to minimize current of the sensor node by using different types of algorithm applied to the radio transmission technique and on how to minimize power consumed by the sensing elements without affecting the accuracy of the data collected. Other research applied algorithm on radio transmission technique are by turning off the radio whenever possible to obtain energy savings. In other hand the sensoring element chosen must be very low energy consumed. The approach taken in this thesis is slightly different compared to other studies. The approach is to focus on the energy storage reservoir. Technically a parallel combination between two different types of energy storage chosen are the rechargeable lithium ion battery and supercapacitor. Supercapacitor are connected in series by using a simple cell balancer, a current regulator is created to give a balance charge and discharge current and charge voltage between the two series. Pulse load which is WSN radio will be supplied by supercapacitor since the capability of supercapacitor in handling pulse current faster due to the ability of faster charged and discharge characteristic giving a more balanced charge and discharge of the battery. The approach here is to create an on/off charging environment, giving the combination of energy storage device (ESD) time to being charged from solar panel through available charger without disturbance from the load. The on/off control from the timer is also used to control the power flow from the ESD, for power enhancement, and to deliver the power to the load efficiently. This improves the battery usage time and WSN nodes operation times. Experiments taken under four different approaches, the first one is control using the initial condition of the load without energy management and three designs with energy managements. The experimental results show that with the combination of on/off technique and the hybrid ( battery and supercapacitor) can achieve much longer runtime for the WSN node. The hybrid are built with one lithium ion battery and six 10F supercapacitor. The supercapacitor is connected two in series in three parallel combination giving total of 15F capacitance. An improvement of 160 % of the operating time for the WSN node is observed. The design presented in this research can be scaled to larger or smaller power capacities for a variety of other applications.